Remediation of Chromium-Contaminated Soil Based on Bacillus cereus WHX-1 Immobilized on Biochar: Cr(VI) Transformation and Functional Microbial Enrichment - Chen, Youyuan (Front Microbiol, 2021)
Microorganisms are applied to remediate chromium (Cr)-contaminated soil extensively. Nevertheless, the microbial loss and growth inhibition in the soil environment restrain the application of this technology. In this study, a Cr(VI)-reducing strain named Bacillus cereus WHX-1 was screened, and the microbial aggregates system was established via immobilizing the strain on Enteromorpha prolifera biochar to enhance the Cr(VI)-reducing activity of this strain. The mechanism of the system on Cr(VI) transformation in Cr-contaminated soil was illuminated. Pot experiments indicated that the microbial aggregates system improved the physicochemical characteristics of Cr-contaminated soil obviously by increasing organic carbon content and cation exchange capacity, as well as decreasing redox potential and bulk density of soil. Moreover, 94.22% of Cr(VI) was transformed into Cr(III) in the pot, and the content of residue fraction Cr increased by 63.38% compared with control check (CK). Correspondingly, the physiological property of Ryegrass planted on the Cr-contaminated soil was improved markedly and the main Cr(VI)-reducing microbes, Bacillus spp., were enriched in the soil with a relative abundance of 28.43% in the microbial aggregates system. Considering more active sites of biochar for microbial aggregation, it was inferred that B. cereus WHX-1 could be immobilized by E. prolifera biochar, and more Cr(VI) was transformed into residue fraction. Cr stress was decreased and the growth of plants was enhanced. This study would provide a new perspective for Cr-contaminated soil remediation.